(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تتكرّر في الشعر الجاهلي كثير من صور البحر , وأمواجه , وسفنه ؛ إذ تتشكل هذه الصّورـ أحياناً ـ في صور جزئيّة في بيت واحد، أو ومضة خاطفة , وأحياناً أخرى في صور فيها بعض التفصيل والإطالة, أو صور كليّة, تجسّد التجربة الأدبيّة الشّاملة للشّاعر؛ إذ تبنى حولها رموز النصّ في علاقات تقابل, أو تبادل الوظائف، والإيحاءات. ولقد رأى البحث أنّ الصّور البحريّة ترد في سياقات ثلاثة؛ إمّا في رحلة الظعائن والناقة؛ إذ تبرز صورة الظعينة السّفينة، والناقة السّفينة. وإمّا في الغزل ؛ إذ تظهر صورة المرأة / الدرّة. وإمّا في معرض الحديث عن الذات الشاعرة المنتشية في أحاديث التغني بالبلاغة، والبيان، والمقدرة في فنّ القول, وفي أحاديث التفاخر بالقوة, والكرم، والعطاء . وحاول البحث تبيان صلة هذه الصّور ببنية القصيدة الجاهليّة, وصلتها بالذات الشاعرة, وبالطبع البشري, بآفاقه النفسية والثقافية. Many images of sea, sea waves and ships is repeated in al-Jahili poetry; sometimes, such images are formulated partially in one single line of verse or as a quick flicker, if not such those detailed or circumlocutory images; other times, they occur as comprehensive images that embody the poet’s collective literary experience, upon which textual symbols are structured in the form of oppositional or substitutive functions and suggestions. This piece of research concludes that such maritime images take place in three contexts: either in the howdahs’ or riding camels journeys in which the image of the ship-howdah or ship-camel appears; or, in love poetry, in which the image of the pearl woman appears. Or, they may occur while disclosing the poetical self when highly indulged in rhetoric, semantics and oration, not to mention vainglory, generosity and hospitality speeches. In brief, this research attempts to explain the relationship of such images to the structure of the al-Jahili poem, the poetical self, the human temperament, and his psychological and cultural horizons.